Sex Role Stereotyping among School Counsellors - Wetmore-Foshay, Anne A.; O'Neill, Patrick; Foster, James A. (Canadian Journal of Counselling and Psychotherapy, 2012)
All school counsellors in the Province of Nova Scotia were mailed the Stereotype Questionnaire and asked to rate a "mature, healthy, socially competent" male, female, or adult. A significant sex difference was found, with women counsellors more likely to use "masculine" traits to describe the healthy person of either sex. This result is discussed in terms of changing attitudes toward sex roles, and the possible selection factors which at- tract women who value traditional "masculine" qualities and men who value "feminine" qualities to the counselling profession.